Quantitative differentiation of tendon and ligament using magnetic resonance imaging ultrashort echo time T2* mapping of normal knee joint. (November 2022) - Okuda, Miho; Kobayashi, Satoshi; Toyooka, Kazu; Yoshimizu, Rikuto; Nakase, Junsuke; Hayashi, Hiroyuki; Ueda, Yu; Gabata, Toshifumi
Background: Ligaments and tendons are difficult to differentiate on conventional magnetic resonance imaging (MRI). Ligaments and tendons are different histologically, and tendon graft ligamentization is known to occur after anterior cruciate ligament (ACL) reconstruction. Purpose: To quantify and differentiate the ultrashort echo time T2* (UTE-T2*) values of normal knee ligaments and tendons using a 1.5-T MRI scanner. Material and Methods: The right knees of 12 healthy volunteers (6 men, 6 women; mean age = 30.8 ± 9.6 years) were scanned using a UTE-T2* sequence and the UTE-T2* values of the proximal, middle, and distal portions of the ACL, posterior cruciate ligament (PCL), and patellar tendon (PT) were evaluated. Two doctors manually drew the regions of interest four times and intra- and inter-observer reliability were evaluated by intraclass correlation coefficients. Results: The UTE-T2* values of ACL at the proximal, middle, distal, and mean were 12.0 ± 2.3, 11.3 ± 2.3, 12.3 ± 2.6, and 11.9 ± 2.4 ms, respectively. The UTE-T2* values of the PCL at each site were 6.9 ± 1.5, 9.0 ± 1.8, 8.8 ± 2.4, and 8.3 ± 2.1 ms, respectively. The UTE-T2* values of the PT at each site were 7.1 ± 1.7, 4.3 ± 1.7, 4.3 ± 1.8, and 5.2 ± 2.1 ms, respectively. Both intra- and inter-observer reliability showed high agreement rates. There were significant differences among the ACL mean, PCL mean, and PT mean, with a P value <0.01 in all cases. Conclusion: This study confirms that UTE-T2* mapping can quantify the ACL, PCL, and PT, and tendons and ligaments can be differentiated using the UTE-T2* values in normal volunteer knee joints.